Computational Design Research in Architecture: The Legacy of the Hochschule für Gestaltung, Ulm. (March 2014) - Neves, Isabel Clara; Rocha, João; Duarte, José Pinto
The use of computational processes in architecture is a widespread practice which draws on a set of theories of computer science developed in the 60s and 70s. With the advent of computers, many of these methodologies were developed in research centres in the USA and the UK. Focussing on this period, this paper investigates the importance of the German Hochschule fur Gestaltung, Ulm (HfG) design school in the early stages of computation in design and architecture. Even though there were no computers in the school, it may be argued that its innovative pedagogy and distinguished faculty members launched analogical computational design methods that can be seen as the basis for further computational approaches in architecture. The paper draws on archive material, as well as at an original interview with Tomas Maldonado, to propose that the remarkable work pursued by Tomas Maldonado (the educational project), Max Bense (information aesthetics) and Horst Rittel (scientific methods) was fundamental in establishing HfG Ulm as the forerunner of computation in architecture.